Copper-Catalyzed One-Pot Synthesis of Thiazolidin-2-imines - Zorba, Leandros P.; Stylianakis, Ioannis; Tsoureas, Nikolaos; Antonios Kolocouris; Georgios C. Vougioukalakis (Journal of Organic Chemistry, 2024)
The synthesis of thiazolines, thiazolidines, and thiazolidinones has been extensively studied, due to their biological activity related to neurodegenerative diseases, such as Parkinson’s and Alzheimer’s, as well as their antiparasitic and antihypertensive properties. The closely related thiazolidin-2-imines have been studied less, and efficient strategies for synthesizing them, mainly based on the reaction of propargylamines with isothiocyanates, have been explored less. The use of one-pot approaches, providing modular, straightforward, and sustainable access to these compounds, has also received very little attention. Herein, we report a novel, one-pot, multicomponent, copper-catalyzed reaction among primary amines, ketones, terminal alkynes, and isothiocyanates, toward thiazolidin-2-imines bearing quaternary carbon centers on the five-membered ring, in good to excellent yields. Density functional theory calculations, combined with experimental mechanistic findings, suggest that the copper(I)-catalyzed reaction between the in situ-formed propargylamines and isothiocyanates proceeds with a lower energy barrier in the pathway leading to the S-cyclized product, compared to that of the N-cyclized one, toward the chemo- and regioselective formation of 5-exo-dig S-cyclized thiazolidin-2-imines.